An Objective Overview of Covid19 Vaccine Situation in India - Jay Sheth; Kshem Prasad; Tapasvi Puwar (National Journal of Community Medicine, 2022)
Entire world was eagerly waiting for the vaccine against SARS-CoV2 ever since Covid19 pandemic started. India is the second largest populous nation and is among the very few nations who has developed a vaccine against SARS-CoV2. India is also a major vaccine producing hub supplying large quantum of vaccines to the rest of the world. Efficacy, advantages and comparison between various covid vaccine has been largely discussed by the scientific community. However, there are various other factors affecting the vaccine situation in a nation, may it be the plan, strategy, it’s implementation, local context, health infrastructure etc. While there are many news and views related to covid-19 vaccine, one need to look beyond & into so many other aspects related to the factors affecting this situation. Through discussion of some of these key factors, we tried to draw an overall picture of the Covid19 vaccine situation in India. Keeping in line with our objective, we keep the focus of our discussion on vaccine development & manufacturing issues, diplomatic decisions on vaccine & the reasons behind the same, international factors etc. We have purposefully restricted our discussion to these factors and did not go in details of the national level policy and its implementation details in this article.